2015
DOI: 10.4012/dmj.2015-045
|View full text |Cite
|
Sign up to set email alerts
|

Influence of light intensity on surface-free energy and dentin bond strength of single-step self-etch adhesives

Abstract: In this study, we investigated the influence of light intensity on the surface-free energy and dentin bond strength of single-step selfetch adhesives. The adhesives were applied to the dentin surfaces of bovine mandibular incisors and cured with light intensities of 0 (no irradiation), 200, 400, and 600 mW/cm 2 . Surface-free energies were determined by measuring the contact angles of three test liquids placed on the cured adhesives. Dentin bond strengths of the specimens were also measured. Polymerization wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…This may be attributed to the adsorption of the so‐called atmospheric contamination layer. It has been reported that the γSd values of oxidized surfaces measured using this method were approximately 40 mN m −1 , whereas those of surfaces coated with polytetrafluoroethylene were approximately 20 mN m −1 . The present study indicated that the γ S , γSp, and γSh values of cured adhesive with an OIL were significantly higher than those of cured adhesives without an OIL.…”
Section: Discussionsupporting
confidence: 44%
“…This may be attributed to the adsorption of the so‐called atmospheric contamination layer. It has been reported that the γSd values of oxidized surfaces measured using this method were approximately 40 mN m −1 , whereas those of surfaces coated with polytetrafluoroethylene were approximately 20 mN m −1 . The present study indicated that the γ S , γSp, and γSh values of cured adhesive with an OIL were significantly higher than those of cured adhesives without an OIL.…”
Section: Discussionsupporting
confidence: 44%
“…This may be attributed to the adsorption of the so-called atmospheric contamination layer, particularly if the surface was activated chemically and/or mechanically (19). In addition, it has been reported that the c d S values of oxidized surfaces measured using this method are, in general, approximately 40 mN m À1 (21,22). The c S , c p S , and c h S for uncured EP did not show any significant differences from those of CA and FS, so the SFE characteristics of the resin composite were not considered to be influenced by type of resin composite.…”
Section: Discussionmentioning
confidence: 96%
“…The SM and CS adhesives showed higher SFE and higher SBS with both resin composites than did the GB adhesive. Optimal wettability is important to enable the materials to spread across the entire surface and to establish adhesion (18)(19)(20)(21)(22)27). Therefore, the maximum bond strength is assumed to occur when the SFE of the adherend surface is maximized.…”
Section: Discussionmentioning
confidence: 99%
“…The γnormalSd of the enamel surface remained relatively constant under all of the conditions tested. It has been reported that many oxidized surfaces have γnormalSd values that are close to 40 mN m −1 . This has been attributed to the ‘atmospheric contamination layer’, particularly if the surface is activated chemically or mechanically .…”
Section: Discussionmentioning
confidence: 99%